EAC power distribution line cable monitoring using state-of-the-art distributed sensing instruments - Ioannou, Andreas; Argyrou, Maria C.; Kouzoupou, Charalambos; Kalli, Kyriacos; Marchesini, Pierpaolo; Mondanos, Michael; Karaulanov, Rumen; Stavrou, Andreas; Dionysiou, Antreas; Agathocleous, Michalis; Stavrakis, Efstathios; Nicolaou, Nicolas; et al. (My University, 2023)
We examine the use of state-of-the-art distributed sensing systems to extract temperature information from the optical fibre infrastructure already of the Electricity Authority of Cyprus power distribution network (~25-year old installation); as a means of optical fibre distributed sensing in the underground cables. The optical fibres are collocated with existing power distribution cables, for the purpose of power line monitoring cable joints that are prone to failure, along with general monitoring for unusual behaviour and potential cable fault conditions. Detection is achieved using DTS: Distributed Temperature Sensors (Silixa Ltd) that use RAMAN-based measurements in combination with BOTDR (Brillouin Optical Time-domain Reflectometry) for high-precision temperature detection. We examine the correlation between the temperature of the power cable with the power consumption provided by the EAC and the weather conditions. Furthermore, our data will give an indication of how important is uniform spacing between power and optical cables. The real-time and continuous monitoring of the temperature of the optical cables through the distributed sensing systems may help identifying abnormal cable behavior (hot spots) and possible future network failures in the power network.
Keywords: distributed sensing; Optical fibres